Exosomes: Emerging Therapy Delivery Tools and Biomarkers for Kidney Diseases. (23rd August 2021) - Jin, Can; Wu, Peipei; Li, Linli; Xu, Wenrong; Qian, Hui
Abstract : Exosomes are nanometer-sized small EVs coated with bilayer structure, which are released by prokaryotic and eukaryotic cells. Exosomes are rich in a variety of biologically active substances, such as proteins, nucleotides, and lipids. Exosomes are widely present in various body fluids and cell culture supernatants, and it mediates the physiological and pathological processes of the body through the shuttle of these active ingredients to target cells. In recent years, studies have shown that exosomes from a variety of cell sources can play a beneficial role in acute and chronic kidney disease. In particular, exosomes derived from mesenchymal stem cells have significant curative effects on the prevention and treatment of kidney disease in preclinical trials. Besides, some encapsulated substances are demonstrated to exert beneficial effects on various diseases, so they have attracted much attention. In addition, exosomes have extensive sources, stable biological activity, and good biocompatibility and are easy to store and transport; these advantages endow exosomes with superior diagnostic value. With the rapid development of liquid biopsy technology related to exosomes, the application of exosomes in the rapid diagnosis of kidney disease has become more prominent. In this review, the latest development of exosomes, including the biosynthesis process, the isolation and identification methods of exosomes are systematically summarized. The utilization of exosomes in diagnosis and their positive effects in the repair of kidney dysfunction are discussed, along with the specific mechanisms. This review is expected to be helpful for relevant studies and to provide insight into future applications in clinical practice.